Multi‐level inverter with combined T‐type and cross‐connected modules. Issue 8 (6th June 2018) - Khenar, Mohammad; Taghvaie, Amir; Adabi, Jafar; Rezanejad, Mohammad
Abstract : This study presents a new topology of switched‐capacitor (SC) multilevel inverter, which is able to step‐up input DC voltage to a multilevel AC waveform. This single source inverter is designed based on series connection of the capacitors that charged by input DC sources through a SC network. The proposed modular inverter uses famous T and cross‐connected modules that can be simply extended to higher output voltages without increasing the amount of total standing voltage and peak inverse voltage of switches. It generates positive and negative voltage levels inherently, which eliminates requirements of H‐bridge inverters that are traditionally used to achieve a bipolar output voltage. Analysis shows that the voltage stress on components, cost, efficiency and losses are kept in acceptable range especially for higher‐voltage levels. Capacitor's voltage self‐balancing is another inherent advantage of this modular topology which leads to simplify control strategy and eliminate excess balancing circuit. Performance of a six‐step proposed structure is evaluated by theoretical analysis, simulation and experimental results.